Enhancement of the cooling capability of a high concentration photovoltaic system using microchannels with forward triangular ribs on sidewalls. (15th September 2018) - Di Capua H, Mario; Escobar, Rodrigo; Diaz, A.J.; Guzmán, Amador M.
Highlights: A microchannel heat sink device (MCHSD) maintains the solar cell temperature <301 K. The hydraulic and thermal performance of an MCHSD with ribs were determined. The direct integration "Solar cell-MCHSD" enhances the thermal performance. Passive cooling systems are not recommended for HCPV. Abstract: Numerical simulations were performed to investigate a microchannel heat sink device as cooling option for a high concentration photovoltaic system. COMSOL Multiphysics 5.1 software is used to solve three-dimensional equations which consider conjugate heat transfer, viscous dissipations, and temperature-dependent-properties. This study investigates the integration of microchannels with complex geometric features on its inner walls into the solar cell structure, to enhance the heat transfer performance of a microchannel heat sink-based active cooling system. Inner sidewall mounted forward triangular ribs are considered in aligned and offset distributions along the microchannel walls. In addition, numerical analysis is developed for a conventional flat plate heat sink integrated to a high concentration photovoltaic system to stablish a baseline solar cell temperature. The numerical results show that a micro-channel heat sink device can control and keep in very low range the solar cell temperature (<301 K). Compared to a smooth microchannel, forward triangular ribs installed on the sidewalls enhance the heat transfer capability. Microchannels with aligned and offset rib distributions increase the Nusselt number between 1.8 and 1.6 times, respectively, and increase the average friction factors between 3.9 and 2.3 times, respectively. The microchannel heat sink device with forward triangular ribs is more efficient and effective at Re ≤ 200, since the pumping power reaches a high percentage of the total power generated by solar cell when Re > 200. At Re = 400, the pumping power reaches 41% and 23% of the total power generated by a multi-junction solar cell in the aligned and offset rib distribution, respectively. The pumping power is greatly reduced while using smooth microchannel, because the maximum pumping power is only 9.5% of the solar cell power at Re = 400, however, the resulting solar cell temperature is slightly higher compared to microchannels with aligned and offset rib configurations. A microchannel heat sink provides a more effective cooling solution compared to a passive flat plate heat sink for a high concentration photovoltaic system. In addition, the possibility of direct integration of a microchannel heat sink into a solar cell structure as proposed in this study, represents an interesting option to feasibly increase thermal performance to a considerable level by maintaining the solar cell temperature in a very low range.